Pengembangan E-Modul IPA Berbasis Pendekatan Saintifik pada Materi Sistem Pencernaan pada Manusia untuk Peserta Didik Kelas VIII SMP - Daimul Hasanah; Nofita Trisna Ditya; laily Rochmawati (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to produce, describe quality, and find out students' responses to E-Module Science Based on Scientific Approach on Digestive System Material for Grade VIII Junior High School. This research includes research and development (R&D) using the ADDIE model from Dick and Carry which consists of five stages, including analyze, design, development, implementation, and evaluation. Data collection techniques using observation, interviews, and questionnaires. The research subjects consisted of 3 science education experts as validators and product assessors; and 10 students as respondents. Data analysis techniques for evaluating the E-Module using V-Aiken and for the readability test by respondents using descriptive statistics. The results of this study include: E-Module Science Based on Scientific Approach on Digestive System Material for Grade VIII Middle School Students; the quality of the E-Modules produced is included in the very good criteria based on the assessments of experts and teachers; as well as students responding strongly to the E-Module being developed.